2010
DOI: 10.1186/1752-1947-4-411
|View full text |Cite
|
Sign up to set email alerts
|

Twin reversed arterial perfusion (TRAP) sequence in association with VACTERL association: a case report

Abstract: IntroductionTwin reversed arterial perfusion (TRAP) sequence is a rare complication of multiple pregnancy caused by defects in early embryogenesis. The pump twin supplies the acardiac recipient twin with blood, and although the pump twin is usually structurally normal, congenital anomalies have sometimes been reported. We report a unique case of twin reversed arterial perfusion sequence with a prenatal diagnosis of VACTERL association in the surviving pump twin.Case presentationA 24-year-old Caucasian woman pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 10 publications
3
17
1
Order By: Relevance
“…Because severe cardiac malformations may not be compatible with extrauterine life, they may be more common in fetal populations (Khoshnood et al, ). However, their prenatal detection rate was low in our study when compared with the detection rate reported in the literature (Gembruch and Hansmann, ; Tongsong et al, ; Miller and Kolon, ; Chen et al, ; Athwal et al, ). In our study, most of the prenatally detected cases survived presumably because they were mainly nonsevere isolated septal defects.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Because severe cardiac malformations may not be compatible with extrauterine life, they may be more common in fetal populations (Khoshnood et al, ). However, their prenatal detection rate was low in our study when compared with the detection rate reported in the literature (Gembruch and Hansmann, ; Tongsong et al, ; Miller and Kolon, ; Chen et al, ; Athwal et al, ). In our study, most of the prenatally detected cases survived presumably because they were mainly nonsevere isolated septal defects.…”
Section: Discussioncontrasting
confidence: 83%
“…The literature reports on the prenatal detection of vertebral anomalies in 16 cases of VACTERL association (Claiborne et al, ; Gembruch and Hansmann, ; McGahan et al, ; Baarsma et al, ; Tongsong et al, ; Miller and Kolon, ; Ardiet et al, ; Gedikbasi et al, ; Athwal et al, ; Chen et al, ). In our study, however, prenatal detection of vertebral malformations was low (12.5%), because they did not include segmentation defects and abnormal curvatures of the spinal cord (Wax et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we present the management of a case of single fetal death of a twin which was discovered during pregnancy and subsequently managed conservatively for 33 more days to improve the chance of fetal survival and then delivered vaginally at term following a successful induction of labour. Similar cases had been reported in other parts of the world which were also managed conservatively until delivery [7][8][9][10].…”
Section: Discussionsupporting
confidence: 67%
“…However, situations may arise sometimes in which caesarean section may be indicated and the rate varies considerably ranging from 19 -92% [12]. In a number of cases reported, delivery was by caesarean section, the indication in most cases being fetal heart rate irregularities [8,9,10]. Cord abnormality (commonly torsion of the umbilical cord) was observed in some of these fetuses and was thought to have caused intrauterine hypoperfusion resulting in the death of a twin.…”
Section: Discussionmentioning
confidence: 99%
“…The early pressure flow in one twin exceeds that of other, leading to the reversal of flow in the umbilical artery of the co-twin. 12,16 ii. The alternative hypothesis is that the acardia is a primary defect in embryogenesis in one twin leads to failure of cardiac development.…”
Section: Discussionmentioning
confidence: 99%